Atroposelective Synthesis of Axially Chiral N‐Arylpyrroles by Chiral‐at‐Rhodium Catalysis - Ye, Chen‐Xi (Angew Chem Int Ed Engl, 2020)
A transformation of fluxional into configurationally stable axially chiral N‐arylpyrroles was achieved with a highly atroposelective electrophilic aromatic substitution catalyzed by a chiral‐at‐metal rhodium Lewis acid. Specifically, N‐arylpyrroles were alkylated with N‐acryloyl‐1H‐pyrazole electrophiles in up to 93 % yield and with up to >99.5 % ee, and follow‐up conversions reveal the synthetic utility of this new method. DFT calculations elucidate the origins of the observed excellent atroposelectivity.